Phonogram (2006), volume 3 ebook The immaterial girl. - Gillen, Kieron (Phonogram (2006), 2018)
The creators of the award-winning THE WICKED + THE DIVINE return to their founding critical smash-hit, PHONOGRAM: THE IMMATERIAL GIRL. In a world where music is magic, phonomancer Emily Aster sold half her personality for power. Now, after a decade of brittle perfection, the deal starts to go bad as the girl behind the screen comes looking for revenge. You'll never look at the "Take On Me" video the same ever again. Includes copious "making of" material. . Author: Kieron Gillen. Illustrator: Jamie McKelvie . 2016 Kieron Gillen Limited & Jamie McKelvie.